Persalinan nyaman: Konsep tempat tidur otomatis berbasis pemrosesan gambar comfortable childbirth: The concept of an automated bed based on image processing - Budiono, Hendri D.S.; Satyajati, Bodhimula (BKS-TM Indonesia, 2024)
In Indonesia, the rate of C-section births has increased to 16.4% in 26 years, exceeding the WHO recommendation of 15%, with 25% of these operations performed without medical emergencies. One of the causes is anxiety about labour pain and intrapartum discomfort. Bar-Lung, short for Babar Lungguh, is an automated birthing table system that supports upright labour. Bar-Lung uses image processing to reconstruct the mother's body geometry from the hips down to obtain the parturient's geometry measurements, then adjusts three main components—Back Lift, Leg Support, and Push Bar—for optimal positioning. Research shows that an upright position can facilitate the pushing process and reduce the durationof the second stage, thereby reducing pain and increasing normal labour. Pregnant women are photographed with a calibrated camera layout and lighting and are shot from the side. The photos are processed to identify key points such as the knees, soles of the feet, and waist, which are then counted in pixels and converted to metric units. The measurement results are used to drive the Bar-Lung, which is equipped with a stable and efficient electric putter actuator. The Back Lift, Leg Support, and Push Bar components can be adjusted automatically or manually for fine tuning, while the Emergency button allows the birthing table position to be reset in case of emergency. The Bar-Lung makes childbirth easier and increases the efficiency of medical personnel, with the potential to reduce the number of Caesarean sections inIndonesia by reducing the duration of labour pain.